Electrical and photoconductivity properties of p-Si/P3HT/Al and p-Si/P3HT:MEH-PPV/Al organic devices: Comparison study - Gunduz, B.; Yahia, I. S.; Yakuphanoğlu, Fahrettin (Elsevier, 2012)
The electrical and photoresponse properties of the p-Si/P3HT/Al and p-Si/P3HT:MEH-PPV/Al organic devices have been investigated by current-voltage and capacitance-voltage characteristics. The diode parameters such as ideality factor, barrier height, rectification ratio, Richardson constant, and series resistance were determined from current-voltage characteristics at different temperatures. The diodes indicate a non-ideal current-voltage behavior due to the ideality factor being higher than unity due to the effect of series resistance and the presence of an interfacial layer. The interface state density D-it values of the P3HT and P3HT:MEH-PPV diodes vary from 1.829 x 10(10) to 3.825 x 10(11) eV(-1) cm(-2) and from 4.561 x 10(11) to 3.233 x 10(12) eV(-1) cm(-2), respectively. The photoconductivity properties of the diodes under various illuminations have been investigated. The photoconductivity parameters of the P3HT:MEH-PPV diode are higher than that of photoconductivity parameters of the P3HT diode. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: P3HT and MEH-PPV organic semiconductors; I-V and C-V measurements; Interface state density; Organic Schottky diode; Rectification ratio; Photoconductivity properties